PENERAPAN TEKNOLOGI COMPRESSION DAN FUEL TESTER UNTUK MENINGKATKAN PRODUKTIVITAS DAN LAYANAN SERVIS SEPEDA MOTOR DI BENGKEL SABAR GARAGE - Nanang Romandoni; Faizin, Kholis Nur; Puspitasari, Indah; Bi Asngali; Gunaputra, Ade Ilham (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2023)
Motorcycles with Electronic Fuel Injection (EFI) technology require special maintenance including maintenance of the electronic control unit (ECU), sensors, actuators (injector and ignition coil), and fuel pump. Therefore, workshops that are engaged in motorcycle maintenance services, such as sabar garage, must continue to upgrade their skills to meet market needs. Based on the analysis of the situation and technical problems at the sabar garage workshop, it was concluded that the mechanics had difficulty measuring the compression ratio and fuel pump pressure. The results of the analysis were then discussed and activities were determined, namely a training program in the form of measuring the compression ratio and fuel pump pressure on motorcycles with EFI technology. This is intended so that sabar garage mechanics are able to operate compression gauges and fuel testers. The training was carried out for 1 day with a practical theoretical method. Partner contributions include providing practical objects, namely motorcycles with EFI technology and tool boxes. The results show that mechanics are able to measure the compression ratio and fuel pump pressure on motorcycles with EFI technology. The expected impact is an increase in service and productivity of the workshop so that it correlates with an increase in the income of the workshop.